Proteomic Analyses of Thioredoxins f and m Arabidopsis thaliana Mutants Indicate Specific Functions for These Proteins in Plants - Juan Fernández-Trijueque; Antonio-Jesús Serrato; Mariam Sahrawy (MDPI AG, 2019)
A large number of plastidial thioredoxins (TRX) are present in chloroplast and the specificity versus the redundancy of their functions is currently under discussion. Several results have highlighted the fact that each TRX has a specific target protein and thus a specific function. In this study we have found that in vitro activation of the fructose-1,6-bisphosphatase (FBPase) enzyme is more efficient when f1 and f2 type thioredoxins (TRXs) are used, whilst the m3 type TRX did not have any effect. In addition, we have carried out a two-dimensional electrophoresis-gel to obtain the protein profiling analyses of the trxf1, f2, m1, m2, m3 and m4 Arabidopsis mutants. The results revealed quantitative alteration of 86 proteins and demonstrated that the lack of both the f and m type thioredoxins have diverse effects on the proteome. Interestingly, 68% of the differentially expressed proteins in trxf1 and trxf2 mutants were downregulated, whilst 75% were upregulated in trxm1, trxm2, trxm3 and trxm4 lines. The lack of TRX f1 provoked a higher number of down regulated proteins. The contrary occurred when TRX m4 was absent. Most of the differentially expressed proteins fell into the categories of metabolic processes, the Calvin–Benson cycle, photosynthesis, response to stress, hormone signalling and protein turnover. Photosynthesis, the Calvin–Benson cycle and carbon metabolism are the most affected processes. Notably, a significant set of proteins related to the answer to stress situations and hormone signalling were affected. Despite some studies being necessary to find specific target proteins, these results show signs that are suggest that the f and m type plastidial TRXs most likely have some additional specific functions.